Periodic copper microbead array on silver layer for dual mode detection of glyphosate - Ramachandran Balaji; Vengudusamy Renganathan; Chia-Pei Chu; Ying-Chih Liao; C.R. Kao; Shen-Ming Chen (Elsevier, 2022)
In this research, periodic Cu microbead arrays on Ag layer (CASS) for dual mode detection of glyphosate (GLP) is developed. CASS is fabricated on screen printed carbon electrodes though electroplating technique and characterized thoroughly to understand the morphology. Average size of Cu bead is 280 µm and distance between beads is found to be 100 µm through scanning electron microscopy (SEM) analysis. Periodicity of Cu microbead arrays enhanced the overall catalytic activity for both electrochemical and SERS modes. Wide detection range of 0.5 - 772.5 μM is obtained for electrochemical mode and a superior enhancement factor in the range of 108 is achieved in SERS mode. Further, both electrochemical and SERS modes showed an excellent limit of detection (10−9 M and 10−11 M) for GLP. Also excellent stability and reproducibility of CASS is observed for electrochemical mode for 10 day period towards GLP detection and with respect to SERS, many random spots on CASS are tested for reproducible GLP SERS signal. CASS sensor promises to be a good prospect for portable, cost effective and on the spot detection of lethal pesticides.